Pengaruh Keputusan Pemilihan Pada Sekolah Islam Terpadu Terhadap Kepuasan dan Positive Word of Mouth - Hafizh Akbar; Simanjuntak, Megawati; Asnawi, Yudha Heryawan (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The number of private schools continues to increase from year to year and affects the competition between schools and stimulated research in educational marketing. This study is to analyze the effect of religiosity, school reputation, product and perceived service quality on parental selection decisions, analyze the influence of parental selection decisions on parental satisfaction, analyze the effect of parental satisfaction on positive word of mouth, and formulating a strategy to improve election decisions, parental satisfaction and positive word of mouth. Data in this study were collected through questionnaires distributed online. Data collection was done by convenience sampling technique and the valid questionnaire results were 183 participants. The analysis uses SEM (structural equation modeling) with LISREL version 8.80 and SWOT to formulate a new strategy. The findings of the study indicate that religiosity, school reputation, product and perceived service quality have a significant effect on parental selection decisions, parental selection decisions have a significant effect on satisfaction, and satisfaction have a significant effect on positive word of mouth. Keywords: religiosity, school reputation, parental selection decisions, satisfaction, positive word of mouth